Paratyphoid fever: including a discussion of the relationships and characteristics of the intermediate members of the typhoid-colon group of bacteria - Overy, Harry (The University of Edinburgh, 1906)
Of my own cases the most interesting is No. 4. I still have hopes of cultivating the organism, for the reactions are very definite.

The passage of sloughs brings it into line with the cases reported by Wells and Scott, and mentioned above.

On my own showing not one of my cases are absolutely conclusive , but I have said enough to to show that they may be accepted with very good reason. With regard to the general subject the work quoted goes to prove without doubt that there is a definite infectie with organisms resembling the bacillus of Eberth,but not identical and not provoking the same symptom although the clinical type very closely resembles a mild attack of typhoid fever.